Application of New COF Materials in Secondary Battery Anode Materials - Miao Jia; Lixin Zhang; Qiong Yuan (Molecules, 2023)
Covalent organic framework materials (COFs), as a new type of organic porous material, not only have the characteristics of flexible structure, abundant resources, environmental friendliness, etc., but also have the characteristics of a regular structure and uniform pore channels, so they have broad application prospects in secondary batteries. Their functional group structure, type, and number of active sites play a crucial role in the performance of different kinds of batteries. Therefore, this article starts from these aspects, summarizes the application and research progress of the COF anode materials used in lithium-ion batteries, sodium-ion batteries, and potassium-ion batteries in recent years, discusses the energy storage mechanism of COF materials, and expounds the application prospects of COF electrodes in the field of energy storage.